2008
DOI: 10.1111/j.1460-9568.2008.06300.x
|View full text |Cite
|
Sign up to set email alerts
|

Spatial and temporal sensitivity degradation of primary visual cortical cells in senescent rhesus monkeys

Abstract: Human visual function declines with age. Much of this decline is mediated by changes in the central visual pathways. In this study we compared the spatial and temporal sensitivities of striate cortical cells in young and old paralysed macaque monkeys. Extracellular single-unit recordings were employed. Our results show that cortical neurons in old monkeys exhibit lower optimal spatial and temporal frequencies, lower spatial resolution and lower high temporal frequency cut-offs than do cells in young adult monk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
49
1
2

Year Published

2011
2011
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 62 publications
(54 citation statements)
references
References 46 publications
2
49
1
2
Order By: Relevance
“…Furthermore, the mean high cut-off spatial frequency of V1 neurons in old cats was significantly lower than that in young ones. These findings are consistent with a previous study on the V1 neurons of old and young adult monkeys [9] , suggesting that age-dependent degradation of selectivity of visual cortical neurons to spatial frequencies of visual stimuli could be generalized to non-primate mammalian species with well-developed visual system. This age-related functional degradation of visual cortical cells may contribute to the visual acuity decline in the aged individuals.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Furthermore, the mean high cut-off spatial frequency of V1 neurons in old cats was significantly lower than that in young ones. These findings are consistent with a previous study on the V1 neurons of old and young adult monkeys [9] , suggesting that age-dependent degradation of selectivity of visual cortical neurons to spatial frequencies of visual stimuli could be generalized to non-primate mammalian species with well-developed visual system. This age-related functional degradation of visual cortical cells may contribute to the visual acuity decline in the aged individuals.…”
Section: Discussionsupporting
confidence: 92%
“…The imbalance between intracortical excitation and inhibition has been suggested to mediate the functional decline of visual cortical cells in the senescent individuals, as supported by the following experimental findings. First, it has been reported that the responsiveness (including the spontaneous activity and visually-evoked response) of visual cortical cells in the old mammalian animals is significantly enhanced compared with that in the young adult animals, while the signal-to-noise ratio of visual cortical cells in the old animals is significantly decreased compared with that in young adults [9,10,15,18] . Second, administration of GABA and GABA A receptors by iontopherosis can significantly improve the function of V1 neurons in the old macaque monkeys, and application of antagonists of GABA A receptors exert a much weaker effect in old than in young monkey cortex [17] .…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Schmolesky, Wang, Pu and Leventhal (2000) found that neurons in V1 of aged macaque monkeys are less direction and orientation selective than those of their younger counterparts, exhibiting increased responses to all directions and orientations and higher spontaneous activity. Liang et al (2008) compared the proportion of directionally-selective V5/MT cells in young and old macaque monkeys and found that the proportion of such cells were lower in old animals. They also found that the degree of direction selectivity was more severely compromised in V5/MT than in V1 of senescent monkeys.…”
Section: Neural Correlatesmentioning
confidence: 99%
“…Indeed, there is neurophysiological evidence to suggest that this may be the case. Zhang, Wang, Wang, et al (2008) have shown that neurons in area V1 of aged rhesus monkeys exhibit reduced high temporal frequency cut-offs and lower optimal temporal frequencies, compared to younger animals. Similarly Yang, Zhang, Liang et al (2009) have provided evidence for a significant degradation of the speed selectivity of motion-sensitive cells in primate V5/MT.…”
Section: Neural Correlatesmentioning
confidence: 99%